Accurate and fast urinalysis in febrile patients by flow cytometry. Issue 5 (4th May 2017) - de Boer, Foppie J.; Gieteling, Elske; van Egmond-Kreileman, Heidi; Moshaver, Bijan; van der Leur, Sjef J.C.M.; Stegeman, Coen A.; Groeneveld, Paul H.P.
Abstract: Background: The urine culture is worldwide accepted as the gold standard in diagnosing urinary tract infections, but is time consuming and costly, other methods are fast but moderately reliable. We investigated whether counting the number of bacteria by flow cytometry could be a fast and accurate method to analyze urine samples in febrile patients at the emergency department (ED). Methods: Urine samples were obtained from 140 febrile patients at the ED. Urinalysis was performed according to standard procedures. Flow cytometric analysis for bacteria was performed with the Accuri C6 flow cytometer. Diagnostic values were determined at various cut-off points by using urine culture as the gold standard. Results: The highest diagnostic accuracy of urinalysis of bacteria was obtained with flow cytometric analysis (AUC of 0.96). The best cut-off value for bacteria counted by flow cytometry based on the ROC-curve was 3.72 × 10 6 bacteria/mL, this resulted in a sensitivity of 94.7% and a specificity of 88.2%. Conclusions: Counting bacteria by flow cytometry has the highest diagnostic accuracy and is superior to other methods in urinalysis in febrile patients in the ED when using urine culture as the gold standard.